Difference in single-leaf and whole-plant photosynthetic response to light under steady and non-steady states in Arabidopsis thaliana - Sakoda, Kazuma; Sakurai, Atsushi; Imamura, Sousuke (Frontiers in Plant Science, 2025)
Although photosynthetic response to light has been extensively studied at the single-leaf level, little is known about the response at the whole-plant level. The present study aims to reveal the differences in the photosynthetic response to light under steady and non-steady states between the single leaf and whole plant in Arabidopsis thaliana and to investigate the mechanisms underlying these differences with respect to leaf aging. First, we developed an open system for gas exchange measurement of the whole plant of Arabidopsis. It enabled the photosynthetic response to dynamic environmental changes to be directly compared between the single leaf and whole plant. The photosynthetic response to the fluctuating light did not differ significantly between the single leaf and whole plant. This result is partly confirmed by the fact that the leaves at different ages showed no difference in the photosynthetic induction after a step change in light. On the other hand, light response analysis for steady-state photosynthesis showed a higher apparent quantum yield in the whole plant than in the single leaf. This difference might be attributed to the difference in the efficiency of light absorption and/or utilization of absorbed light among the leaves at different ages.